2019
DOI: 10.1186/s12903-019-0842-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgery-first approach on the oral health-related quality of life: a systematic review and meta-analysis

Abstract: Background The oral health-related quality of life (OHRQoL) is affected by dentofacial deformity. Patients with dentofacial deformity are normally treated with orthognathic surgery, including conventional three-stage method (CTM) and surgery first approach (SFA). The aim of this systematic review and meta-analysis was to compare the impact of SFA with CTM on the OHRQoL of patients with severe dentofacial deformity. Methods Five English databases, three Chinese databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…Some of them are eager to improve their facial aesthetics and want to prevent the progressive deterioration of their facial appearance that can occur with presurgical orthodontics. A meta-analysis on the impact of the SFA indicated that SFA can immediately and persistently contribute to better oral health-related quality of life in patients with dentofacial deformities[ 20 ]. The SFA not only promotes rapid improvement in facial appearance but also considerably reduces the overall treatment time by eliminating the time-consuming presurgical orthodontic stage and facilitating tooth movement after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them are eager to improve their facial aesthetics and want to prevent the progressive deterioration of their facial appearance that can occur with presurgical orthodontics. A meta-analysis on the impact of the SFA indicated that SFA can immediately and persistently contribute to better oral health-related quality of life in patients with dentofacial deformities[ 20 ]. The SFA not only promotes rapid improvement in facial appearance but also considerably reduces the overall treatment time by eliminating the time-consuming presurgical orthodontic stage and facilitating tooth movement after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…approach than surgery-first noncleft-orthognathic surgery approach, which clinically represents the cleft-associated dental anomalies and transverse maxillary collapse. The optimal balance between esthetic and functional outcomes, significant reduction in total treatment time, and high rates of patient satisfaction have led to the postulation that the modern surgery-first orthognathic-approach concept may denote a reasonable and cost-effective pathway to manage dentoskeletofacial deformities, and has the potential to become the first-line orthognathic-surgery intervention in the future [18][19][20]. Despite published recommendation for selection of patients for the surgery-first approach [22,23], there are no unique criteria adopted by different centers and clinicians [15][16][17][18][19][20]24,[27][28][29][30][31][45][46][47][48][49][50][51][52][53].…”
Section: Primary Endpointmentioning
confidence: 99%
“…The optimal balance between esthetic and functional outcomes, significant reduction in total treatment time, and high rates of patient satisfaction have led to the postulation that the modern surgery-first orthognathic-approach concept may denote a reasonable and cost-effective pathway to manage dentoskeletofacial deformities, and has the potential to become the first-line orthognathic-surgery intervention in the future [18][19][20]. Despite published recommendation for selection of patients for the surgery-first approach [22,23], there are no unique criteria adopted by different centers and clinicians [15][16][17][18][19][20]24,[27][28][29][30][31][45][46][47][48][49][50][51][52][53]. While some patterns of presentation (e.g., Class III prognathism with open bite) have been considered as good candidates for the surgery-first approach, a wide spectrum of dental configurations have also been contemplated for surgery-first orthognathic surgery treatment [15][16][17][18][19][20][22][23][24][27][28][29][30][31][45]…”
Section: Primary Endpointmentioning
confidence: 99%
See 2 more Smart Citations